The Relationship between Work Shift and Burnout in Golestan Hospital in Ahvaz - Fatemeh Javaherforoush zadeh1; laleh gharacheh (Shahid Sadoughi University of Medical Sciences, 2020)
Background: The occupational burnout affects the individuals' physical and mental health and is observed in many occupations as a final outcome  among nurses. The aim of this study was to investigate the relationship between nurses' work shift and burnout in Golestan Hospital in Ahvaz City. Methods: This descriptive- analytical study was conducted over all personnel (280 persons) of Golestan Hospital in Ahvaz. The study participants were selected from personnel with at least one year of continuous shift work experience in both shifts as well as day shift groups in 2019. Results: The prevalence of occupational burnout was 14.3% (40 persons) in the morning shifts and 85.7% (240 persons) in the group who worked in both shifts. Regarding the occupational burnout components, the prevalence rates of emotional exhaustion, depersonalization, and personal accomplishment were 60.7% (n = 170), 78.6% (n =220), and 46.4% (n = 130), respectively.  Shift work had a significant with emotional exhaustion (P <0.01) and depersonalization (P <0.01). Conclusion: Considering different levels of occupational burnout in nurses, managers of the health system are suggested to analyze the nurses' needs in order to increase the facilities, study the supply and distribution of human resources in the medical departments, and provide the minimum job security for personnel and nurses.